Proteomic analysis identified LBP and CD14 as key proteins in blood/biphasic calcium phosphate microparticle interactions. (June 2021) - Jing, Lun; Rota, Solène; Olivier, Florian; Momier, David; Guigonis, Jean-Marie; Schaub, Sébastien; Samson, Michel; Bouler, Jean-Michel; Scimeca, Jean-Claude; Rochet, Nathalie; Lagadec, Patricia
Abstract: Immediately upon implantation, scaffolds for bone repair are exposed to the patient's blood. Blood proteins adhere to the biomaterial surface and the protein layer affects both blood cell functions and biomaterial bioactivity. Previously, we reported that 80-200 µm biphasic calcium phosphate (BCP) microparticles embedded in a blood clot, induce ectopic woven bone formation in mice, when 200-500 µm BCP particles induce mainly fibrous tissue. Here, in a LC-MS/MS proteomic study we compared the differentially expressed blood proteins (plasma and blood cell proteins) and the deregulated signaling pathways of these osteogenic and fibrogenic blood composites. We showed that blood/BCP-induced osteogenesis is associated with a higher expression of fibrinogen (FGN) and an upregulation of the Myd88- and NF-κB-dependent TLR4 signaling cascade. We also highlighted the key role of the LBP/CD14 proteins in the TLR4 activation of blood cells by BCP particles. As FGN is an endogenous ligand of TLR4, able to modulate blood composite stiffness, we propose that different FGN concentrations modify the blood clot mechanical properties, which in turn modulate BCP/blood composite osteoactivity through TLR4 signaling. The present findings provide an insight at the protein level, into the mechanisms leading to an efficient bone reconstruction by blood/BCP composites. Statement of significance: Upon implantation, scaffolds for bone repair are exposed to the patient's blood. Blood proteins adhere to bone substitute surface and this protein layer affects both biomaterial bioactivity and bone healing. Therefore, for the best outcome for patients, it is crucial to understand the molecular interactions between blood and bone scaffolds. Biphasic calcium phosphate (BCP) ceramics are considered as the gold standard in bone reconstruction surgery. Here, using proteomic analyses we showed that the osteogenic properties of 80-200 µm BCP particles embedded in a blood clot is associated with a higher expression of fibrinogen. Fibrinogen upregulates the Myd88- and NF-κB-dependent TLR4 pathway in blood cells and, BCP-induced TLR4 activation is mediated by the LBP and CD14 proteins. Graphical abstract: Image, graphical abstract